“Incorporación de compuestos bioactivos de cascarilla de cacao (theobroma cacao l.). En queso semi-maduro tipo tilsit” - Cervantes Guillen, José Eduardo (2022)
Bioactive components are found in small amounts in food. Although they are considered non-nutritional ingredients, they are of vital importance for the maintenance of human health. The development of this research project seeks to incorporate bioactive compounds from cocoa husks (Theobroma cacao L.) in Tilsit-type semi-mature cheese with technological and innovative and possibly functional purposes. The application of this ingredient in a substitute product for Tilsit-type semi-mature cheese will allow